The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1007/s10800-008-9600-9
|View full text |Cite
|
Sign up to set email alerts
|

Role of alloyed silicon and some inorganic inhibitors in the inhibition of meta-stable and stable pitting of Al in perchlorate solutions

Abstract: The study of both meta-stable and stable pitting events on the surface of pure Al and three Al-Si alloys, namely (Al + 6%Si), (Al + 12%Si) and (Al + 18%Si) alloys, was carried out in deaerated neutral NaClO 4 solutions of various concentrations (10 -4 -10 -2 M). Measurements were carried out under the effect of various experimental conditions using potentiodynamic anodic polarization and potentiostatic techniques. The results presented below showed that meta-stable pits (appeared as oscillations in current) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Concerning the effect of silicon, no noticeable difference is detectable. However, all the previous research has indicated the positive effect of silicon on the pitting resistance of aluminum alloys [29,59,60]. Nevertheless, it is worth mentioning that these studies are focused on silicon content higher than 6%, which is higher than the percentage of silicon in both of our alloys.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 80%
“…Concerning the effect of silicon, no noticeable difference is detectable. However, all the previous research has indicated the positive effect of silicon on the pitting resistance of aluminum alloys [29,59,60]. Nevertheless, it is worth mentioning that these studies are focused on silicon content higher than 6%, which is higher than the percentage of silicon in both of our alloys.…”
Section: Electrochemical Impedance Spectroscopymentioning
confidence: 80%
“…4 that passive film is stable until the potential is increased to above a certain critical potential value, known as the pitting potential (E P ). Passivity is due to the presence of an Al 2 O 3 film on the surface of the specimens [25]. By increasing potential in the passive region fluctuation of current is not considerable (characteristic of the passive region) until passivity breaks down at E P leading to pit initiation.…”
Section: Resultsmentioning
confidence: 99%
“…This incorporation precludes significant dissolution of the oxide film [25]. Firm oxide film formation depends on the shape of silicon particles.…”
Section: °C 600°cmentioning
confidence: 99%
“…Accordingly, the properties of the oxide film are important only during the first stages of localized corrosion, but once the pit propagation stage has been reached the electrochemical properties of the surface phases take control of the pitting process [25]. In this work the decrease in pitting susceptibility concurrent with the increase in Si/Mg molar ratio is due, in part, to an improvement in the resistance of the oxide film due to a beneficial effect of silicon addition (taking as a reference observations for Al-Si alloys by our group [26] and by other authors [27,28]); however, a full elucidation of the dominating mechanism would require further investigation to reveal changes in composition and electronic properties of passive films on the different materials. In addition, application of in situ local techniques such as atomic force microscopy and scanning electrochemical microscopy [29] and also of the pit propagation rate technique would be desirable to correlate the location of initiation sites with microstructural features [30].…”
Section: Resultsmentioning
confidence: 57%